The Reasons of Errors That Change The Meaning in The Subject of Holy Quran Memorization from TheUniversity Science Islam Malaysia Students’ Perception - Ahmed Abedalqader Hasan Qatanany; Samer Najeh Abdullah Samarh; Muhammad Hafiz Saleh; Abdoul Karim Toure (USIM Press, 2024)
Journal of Quran Sunnah Education and Special Needs (JQSS) Volume 7 Issue 2 Page (163-174)